A survey on biometric based crypto techniques - Ruth Ramya, K; Saahithi, S; Gnaneswar, T; Afsar Jaha, SD (International Journal of Engineering and Technology, 2018)
The biometric based crypto techniques extract the features from grayscale images and use those features in encryption process i.e., key will be generated from extracted features. In attribute based crypto-systems attributes of the user like email, usernames etc.â€¦will be treated as a public key. Secret key is associated with each attribute i.e. for email there will be a secret key and for username there will be another secret key. In biometric based crypto systems, an access policy is built from the extracted biometric features.Â Â